Clinical and obstetric characterization of high-risk pregnant women attended at the reference center of the Carajás region-Pará (Research, Society and Development, 2021)
Pregnancy is never risk free. Thus, the realization of prenatal care becomes essential both for the pregnant woman, in order to take care of her health and that of the fetus, and for the Government, to act fully in the promotion, prevention and recovery of this patient. However, a smaller number of pregnant women have particularities that can complicate pregnancy, forming the category of high-risk pregnancy. Thus, this study aims to characterize the clinical and obstetric profile of pregnant women attended at the high-risk prenatal service in a municipality in the region of Carajás. This study is a descriptive research with a quantitative approach. The sample consisted of 213 pregnant women in high-risk prenatal care in a municipality in the Carajás region in southeastern Pará from January to August 2021. The following data were analyzed: age group, quarter in which they were admitted to the service, number of pregnancies, number of abortions, personal history and reason for referral. The average age of the pregnant women was 29.34 years and 77% of them were multiparous, most of the pregnant women (45.5%) were admitted to the service in the second trimester of pregnancy and 40.5% were in the third trimester, most of them had no prior comorbidity. As for the reason for referral, the most prevalent comorbidities were gestational diabetes and hypertensive syndromes. The study was able to describe the clinical-obstetric characteristics, aiming at an improvement in the conditions of prenatal care in the city of Marabá, aiming at a better outcome of pregnancies.